Spoken Registers of Quechua and Discrimination in the Southern Andes - Mannheim, Bruce (2022)
The Southern Quechua language, as spoken in the six southeastern departments of Peru varies not only geographically, but also by socially regimented registers associated with differently positioned speakers, distinguished by phonology, syntax, lexical semantics, and pragmatics. Articulatory phonetics is especially salient: Speakers whose first and primary language is Quechua use a narrow buccal aperture, while speakers for whom Spanish is the primary language but who also speak Quechua use a wider buccal aperture. The distinction between narrow and wide aperture indexes distinct social positionalities (“race,” occupation, social class, gender), and gives rise to an indexical order, each iteration at larger social scales, which feeds and is fed by local, regional, and national racist stereotype. Here it is critical to keep in mind Eckert’s (2014, p. 23) observation that social indices are not “passively inherited” but “are the results of the accumulation of indexical activity at the local level.”